2018
DOI: 10.1515/biol-2018-0033
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the In Vitro Gas Production and Potential Feed Value of Olive, Mulberry and Sour Orange Tree Leaves

Abstract: This study was conducted to determine the potential nutritive value and in vitro gas production (IVGP) parameters of Olea europaea L. (Olive = OL), Morus alba L. (Mulberry = ML) and Citrus aurantium L. (Sour orange = SOL) tree leaves. Hohenheim gas test was used to determine the in vitro gas productions of the leaves. The gas production of samples over time was recorded for 3, 6, 9, 12, 24, 48, 72 and 96 h after incubation. Completely Randomized Design was used to compare gas production, and gas production kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 29 publications
2
8
0
Order By: Relevance
“…Under this study, the R : C had a significant increase in gas volume when roughage level was decreased and concentrate level was increased from 100 to 30 and from 0 to 70%, respectively. Under this study, BP had no significant impacts on a , b , c and a + b values, while R : C did and similar results were also found by other researchers 24 . Plants and feeds containing PTNs, such as CT and SP have demonstrated a wide spectrum of antibacterial properties against rumen bacteria, protozoa, and fungi 23 …”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Under this study, the R : C had a significant increase in gas volume when roughage level was decreased and concentrate level was increased from 100 to 30 and from 0 to 70%, respectively. Under this study, BP had no significant impacts on a , b , c and a + b values, while R : C did and similar results were also found by other researchers 24 . Plants and feeds containing PTNs, such as CT and SP have demonstrated a wide spectrum of antibacterial properties against rumen bacteria, protozoa, and fungi 23 …”
Section: Discussionsupporting
confidence: 86%
“…Under this study, BP had no significant impacts on a, b, c and a + b values, while R:C did and similar results were also found by other researchers. 24 Plants and feeds containing PTNs, such as CT and SP have demonstrated a wide spectrum of antibacterial properties against rumen bacteria, protozoa, and fungi. 23 The DM and NDF degradabilities were remarkably enhanced at both 12 and 24 h of fermentation duration.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were also reported by Olfaz et al, (2018) and Jayanegara et al, (2009). There were positive relationships between ether extract and crude protein with DOI: http://dx.doi.org/10.14203/ann.bogor.2020.v24.n1.50-58 potential gas production, gas production rate, and OMD.…”
Section: Discussionsupporting
confidence: 86%
“…Consequently, some of the shrubs, thorny plants and tree leaves can be used as alternative forages, especially in the wintertime [ 1 , 2 , 3 ]. It is believed that guar bean (Cluster bean = Cyamopsis tetragonoloba ) will contribute to closing the forage gap [ 4 ]. Forage needs of ruminants are provided for by drying or ensiling hay in winter.…”
Section: Introductionmentioning
confidence: 99%
“…Some phenolic compounds are present in the guar bean seeds [ 8 ] and for this reason, it is recommended to use guar bean silage (GS) in ruminant nutrition. Fresh guar beans has shown very good nutritional composition (CP 3.54%, EE: 0.64%, NFE: 11.86%, NDF: 11.69% for dry matter 25.5%) [ 4 ]. It is reported that guar forage is unpalatable and not suitable for grazing but sometimes it can be used to reduce the risk of bloat in grazing ruminants [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%